Kajian Yuridis Perlindungan Data Pribadi Bersifat Umum Dalam Tindak Pidana Kartu Kredit - Silfiya Dewi Febriyanti; Arista Candra Irawati (Journal of Innovative and Creativity, 2025)
The advancement of digital technology has significantly increased the use of credit cards in various financial transactions. However, this development has also led to a rise in cybercrimes, particularly the misuse of general personal data such as name, address, and identification number in credit card fraud. This study conducts a juridical analysis of the legal protection for general personal data in the context of credit card-related criminal offenses in Indonesia. Using a normative legal research method, the study examines the legal framework provided by Law No. 27 of 2022 on Personal Data Protection (PDP Law), in conjunction with the Indonesian Penal Code (KUHP) and other relevant regulations in the financial sector. The findings reveal that although general personal data is not classified as sensitive data, its unauthorized use can lead to severe financial and legal consequences. Legal protection for such data remains inadequate in practice, mainly due to gaps in law enforcement and limited public awareness. Therefore, the study emphasizes the need for stronger regulatory implementation, improved data security measures, and increased legal literacy to effectively combat credit card crimes involving data thef.